2022
DOI: 10.3390/pathogens11050490
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Polymorphisms in Codons 167, 198 and 200 of All Seven β-Tubulin Isotypes of Benzimidazole Susceptible and Resistant Parascaris spp. Specimens from Australia

Abstract: Benzimidazoles resistance is widespread in strongyle parasitic nematodes and associated with polym orphisms in the codons 167, 198 and 200 of isotype 1 β-tubulin (tbb-1). In ascarids, benzimidazole (BZ) resistance has rarely been reported and in none of these cases were any of these polymorphisms detected. Here, available genome and transcriptome data from WormBase ParaSite were used to compare the complete β-tubulin reservoirs of Parascaris univalens, Ascaris suum and Ascaris lumbricoides. Adult Parascaris sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
2
2
1
Order By: Relevance
“…trichiura isotype 1 to sit within a clade with A. suum isotype E and C. elegans isotype 4 (4). Finally, the relationship between ascarid isotype F and strongyle isotype 3 and between ascarid isotype E and strongyle isotype 4 matches that seen previously with these isotypes forming their own clade (7,9,49). There are several possible causes for the differences seen between our phylogeny and those previously published such as the method used to construct the phylogeny, or the sequences used.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…trichiura isotype 1 to sit within a clade with A. suum isotype E and C. elegans isotype 4 (4). Finally, the relationship between ascarid isotype F and strongyle isotype 3 and between ascarid isotype E and strongyle isotype 4 matches that seen previously with these isotypes forming their own clade (7,9,49). There are several possible causes for the differences seen between our phylogeny and those previously published such as the method used to construct the phylogeny, or the sequences used.…”
Section: Discussionsupporting
confidence: 79%
“…isotype 1 and 2 clusters were found to be at a basal position within the larger A, C, D, B, and G clade, whereas in our phylogeny, we see them form a separate clade (7,9,49). Within this clade, the relationship between the strongyles and C. elegans corresponds to previous work with C. elegans isotypes 1 and 2 being closely related to but isolated from strongyle isotype 1 and C. elegans ben-1 being basal to this clade.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Resistance to the BZDs has been commonly reported in the equine industry worldwide (Matthews, 2014 ) and in wild equids (Kuzmina et al ., 2020 ), showing that resistance against this anthelmintic drug class is not always associated with the intensity of anthelmintic treatments. In horse strongyle infection, resistance to the BZDs has been associated with the polymorphisms of codons 167, 168 and 200 of isotype 1 β -tubulin (Ishii et al ., 2017 ; Özben et al ., 2022 ). In horses, since 2000, AR against BZDs has been evaluated in 58 studies and it was reported in all of them (Nielsen, 2022 ).…”
Section: Ar In Equids: Horses Vs Donkeysmentioning
confidence: 99%